Digital capabilities driving industry 4.0 and 5.0 transformation: Insights from an interview study in the maintenance domain - Kans, Mirka; Campos, Jaime (Journal of open innovation, 2024)
This study examines the role of digital capabilities in facilitating organizational transformation within the maintenance domain, focusing on the need for transitioning from Industry 4.0 to Industry 5.0. The evolving concept of Industry 5.0 complements Industry 4.0 by shifting the focus from automation to human-machine collaboration. Industry 5.0 aims to create a more cooperative relationship between humans and machines to maximize productivity and innovation. To facilitate digital transformation, companies need to develop suitable digital capabilities. Through interviews with maintenance specialists and practitioners, we identified key challenges and facilitators to implementing emerging technologies. Key findings highlight the importance of providing high-quality education, aligning digital tools with work tasks, and offering user-friendly digital solutions. Furthermore, the findings emphasize the need for robust information sharing, cooperation, and the formalization of responsibilities between maintenance and production functions. Lastly, establishing a clear digital strategy, commitment to investments, and testing new technologies are crucial for facilitating digital transformation and promoting a culture of innovation.